Factores que limitan las exportaciones de prendas de vestir de mujeres en un e-market place dirigidos a microempresarios de Gamarra - Guerra Rodríguez, Diana Milagros (2021)
The following paper aims to analyze the factors that limits entrepreneurs to export women´s clothing trough an e-market place within the Gamarra commercial emporium in the district of La Victoria in Metropolitan Lima. Cuantitive research was considered to collect information independently through surveys. This research was made with a probabilistic sample of 378 companies, with a confidence level of 95% and a margin of error of 5%. With the data obtained through the surveys, the variables that limits entrepreneurs to export women´s clothing trough an e-market place of export of were analyzed. These variables refer to the lack of time of the entrepreneurs for the implementation of an emarket place, the lack of managerial capacity and the level of logistics quality for order delivery. It is concluded that the variables do limit entrepreneurs to export women´s clothing trough an e-market place.